Dow Chemical Company saran film manufacturing facilities - Dow Chemical Company (1951)
General view of employees at work in the Dow Chemical Company's saran film manufacturing facilities in Midland, Michigan. Initially developed for the U.S. Army to wrap arms and equipment for transport during World War II, saran plastic was subsequently developed and marketed as Saran Wrap for household use.
Keywords: Plastics; Employees; Industries; Dow Chemical Company; Plastics industry and trade; Machinery